PENGARUH SISTEM AKUNTANSI PEMERINTAH DAERAH, PENGENDALIAN AKUNTANSI, KETAATAN PADA PERATURAN PERUNDANGAN DAN SISTEM PELAPORAN TERHADAP AKUNTABILITAS KINERJA INSTANSI PEMERINTAH (AKIP) (Studi Empiris Pada OPD Kabupaten Rokan Hilir) - Chaira Astami Putri Br.Butar-Butar; Yesi Mutia Basri; Al Azhar A (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2018)
This study aims to determine the effect of the application of local government accounting systems, accounting controls, compliance with legislation on the performance of government accountability rokan downstream. The population in this research is 28 units of Rokan Hilir work. Samples taken as many as 127 respondents. The type of data used is primary data with data collection method using questionnaire. Data analysis method used in this research is multiple regression. The result of the research shows that the independent variable in this research is the accounting system of local government partially have influence of significance to accountability of government institution performance, partial accounting control also have influence of significance to accountant performance of government institution, obedience to regulation and reporting system by partial have influence significance to the performance accountability of government agenciesKeywords : Local Government Accounting System, Accounting Controls, Obedience to Laws Regulation Against Accountability and Reporting Systems of Government Institutions.